2015
DOI: 10.1111/jcpp.12430
|View full text |Cite
|
Sign up to set email alerts
|

Contextual variation in young children's observed disruptive behavior on the DBDOS: implications for early identification

Abstract: Background Contextual variation in child disruptive behavior is well documented but remains poorly understood. We first examine how variation in observed disruptive behavior across interactional contexts is associated with maternal reports of contextual variation in oppositional-defiant behavior and functional impairment. Second, we test whether child inhibitory control explains the magnitude of contextual variation in observed disruptive behavior. Methods Participants are 497 young children (mean age = 4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
(51 reference statements)
3
36
0
Order By: Relevance
“…Self‐regulation holds almost unparalleled importance to mental health. Poor SR in some form is related to attention deficit/hyperactive disorder (ADHD) and internalizing and externalizing psychopathology (Calkins, Graziano, & Keane, ; Eisenberg et al., ; Espy, Sheffield, Wiebe, Clark, & Moehr, ; Martel & Nigg, ; Olson, Sameroff, Kerr, Lopez, & Wellman, ; Petitclerc et al., ; Rothbart & Bates, ; Wakschlag et al., ), addiction (Zucker, Heitzeg, & Nigg, ), depression (Wang, Chassin, Eisenberg, & Spinrad, ), bipolar disorder risk (Tseng et al., ), schizophrenia, autism spectrum disorder, obsessive–compulsive and habit disorders (Fineberg et al., ), eating disorders, some personality disorders (Nigg, Silk, Stavro, & Miller, ), and others. Processes of SR are integral to the emergence of psychopathology (Rothbart, ).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐regulation holds almost unparalleled importance to mental health. Poor SR in some form is related to attention deficit/hyperactive disorder (ADHD) and internalizing and externalizing psychopathology (Calkins, Graziano, & Keane, ; Eisenberg et al., ; Espy, Sheffield, Wiebe, Clark, & Moehr, ; Martel & Nigg, ; Olson, Sameroff, Kerr, Lopez, & Wellman, ; Petitclerc et al., ; Rothbart & Bates, ; Wakschlag et al., ), addiction (Zucker, Heitzeg, & Nigg, ), depression (Wang, Chassin, Eisenberg, & Spinrad, ), bipolar disorder risk (Tseng et al., ), schizophrenia, autism spectrum disorder, obsessive–compulsive and habit disorders (Fineberg et al., ), eating disorders, some personality disorders (Nigg, Silk, Stavro, & Miller, ), and others. Processes of SR are integral to the emergence of psychopathology (Rothbart, ).…”
Section: Introductionmentioning
confidence: 99%
“…() found mother–teacher agreements on the oppositionality of young children were higher when parents were asked to rate the behaviour of their children within the school context. It has also been found that the disruptive behaviour of preschoolers when interacting with parents and with unfamiliar examiners in an experimental situation differentially predicts context‐specific reports of oppositionality (Petitclerc et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using observational behavior assessments have shown that children's interactions with researchers and their parents generally align with reports of behavior problems in school and at home, respectively (De Los Reyes, Henry, Tolan, & Wakschlag, 2009;Gray et al, 2012;Petitclerc et al, 2015). Specifically, the Disruptive Behavior Diagnostic Observation Schedule (DB-DOS) is an observational paradigm that elicits behavioral and emotional dysregulation by placing children in challenging situations with different interactional partners and varying levels of adult support.…”
Section: Early Adversity Psychopathology and Emotion Regulationmentioning
confidence: 99%